(untitled) (Maharaja Surajmal Institute Law Journal, 2026)
Gig platforms craft adhesion contracts, classifying 15 million Indian work ers as “partners,” thereby denying social security under Code on Social Security 2020, despite the Gig Workers Act 2026 mandating 1-2% turnover contributions, while COVID lockdowns triggered Section 56 impossibility claims rejected in 70% High Court cases protecting platforms that surged revenues through algorithmic pricing. This doctrinal analysis exposes structural imbalances where platforms control ratings deactivation, and data flows mimicking employment per IFAT v Union of India, yet evade welfare obligations as NITI Aayog reports 40% workers earn below ₹15,000 monthly. Findings advocate EU-style reclassification at 50% control thresh olds, mandatory transparency audits, DPDP data portability, and escrow welfare funds, ensuring India’s ₹2.35 lakh crore gig economy delivers equity for 23.5 million workers by 2030 rather than exploitation.